Abdominal Distention and Acute Urinary Retention secondary to Congenital Distal Vaginal Obstruction in a Newborn Female - Ameen, Nian Noori; Ameen, Nian Noori; Mohammed, Mohammed Kamil (AL-Kindy College Medical Journal, 2009)
Congenital distal vaginal obstruction is usually asymptomatic in a newborn female. On rare occasions, it may present as an acute emergency with life threatening complications.This paper is reporting the rare condition of two newborn females presenting urgently with abdominal distension and acute urinary retention as a result of congenital distal vaginal Obstruction. The case history and urgent management shall be presented and both conditions shall be discussed.